Water-Permeable Dialysis Membranes for Multi-Layered Microdialysis System - To, Naoya; Sanada, Ippei; Ito, Hikaru; Prihandana, Gunawan S.; Morita, Shinya; Kanno, Yoshihiko; Miki, Norihisa (Frontiers in Bioengineering and Biotechnology, 2015)
This paper presents the development of water-permeable dialysis membranes that are suitable for an implantable microdialysis system that does not use dialysis fluid. We developed a microdialysis system integrating microfluidic channels and nanoporous filtering membranes made of polyethersulfone (PES), aiming at a fully implantable system that drastically improves the quality of life of patients. Simplicity of the total system is crucial for the implantable dialysis system, where the pumps and storage tanks for the dialysis fluid pose problems. Hence, we focus on hemofiltration, which does not require the dialysis fluid but water-permeable membranes. We investigated the water-permeability of the PES membrane with respect to the concentrations of the PES, the additives, and the solvents in the casting solution. Sufficiently water-permeable membranes were found through in vitro experiments using whole bovine blood. The filtrate was verified to have the concentrations of low-molecular-weight molecules, such as sodium, potassium, urea, and creatinine, while proteins, such as albumin, were successfully blocked by the membrane. We conducted in vivo experiments using rats, where the system was connected to the femoral artery and jugular vein. The filtrate was successfully collected without any leakage of blood inside the system and it did not contain albumin but low-molecular-weight molecules whose concentrations were identical to those of the blood. The rat model with renal failure showed 100% increase of creatinine in 5 h, while rats connected to the system showed only a 7.4% increase, which verified the effectiveness of the proposed microdialysis system.